THE ROLE OF WHITE BLOOD CELL COUNT IN PERIANAL PATHOLOGIES: A RETROSPECTIVE ANALYSIS OF HEMATOLOGIC MALIGNANCIES - Bedrettin Orhan; Fahir Özkalemkaş; Vildan Özkocaman; Büşra Gürbüz; Tuba Ersal; İbrahim Ethem Pınar; Cumali Yalçın; Ömer Candar; Sinem Çubukçu; Tuba Güllü Koca; Rıdvan Ali (Mediterranean Journal of Hematology and Infectious Diseases)
Background and Objective: Perianal pathologies are the most common cause of perianal infections in patients with hematological malignancies. Perianal infection diagnosis in this group of patients is difficult, thus careful anorectal examination is necessary, with imaging modalities. The literature revealed a knowledge gap on the approach of anal pathologies in patients with neutropenia during diagnosis or chemotherapy. This study aimed to examine our institutional data of perianal complications and investigate the relationship among the white blood cell-neutrophil count, perianal lesion, and the type of treatment in patients with hematologic malignancies during the neutropenic period.